Dead to you - McMann, Lisa. (New York : Simon Pulse, 2012)
Having been abducted at age seven, abandoned, a foster child, and homeless, Ethan, now sixteen, is happy to be home until his brother's suspicion and his own inability to remember something unspeakable from his early childhood begin to tear the family apart.
Keywords: Dysfunctional families -- Fiction; Identity -- Fiction; Family life -- Minnesota -- Fiction; Memory -- Fiction; Kidnapping -- Fiction; Minnesota -- Fiction